2001
DOI: 10.1034/j.1399-6576.2001.045003385.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of colloid fluids on polymorphonuclear granulocyte function in vivo

Abstract: Application of colloids like HA, GEL, or HES in moderate amounts shows no short-term effect on adhesion or activation molecules on granulocytes. However, in high doses, infused in situations such as multiple trauma and sepsis, the consequences on the function of PMN may be speculative and require further investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Clinical studies showed blood transfusion to be an independent risk factor for postinjury MOF (10,11). Animal studies demonstrated that different types of resuscitation fluids may affect the inflammatory response and be involved in the pathogenesis of later MOF (9,(14)(15)(16).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Clinical studies showed blood transfusion to be an independent risk factor for postinjury MOF (10,11). Animal studies demonstrated that different types of resuscitation fluids may affect the inflammatory response and be involved in the pathogenesis of later MOF (9,(14)(15)(16).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies showed that some artificial colloids have additional immune modulation functions besides volume expansion (14,15). Compared with albumin, hydroxyethyl starch (HES) can reduce splanchnic ischemia and release of circulating adhesion molecules in critically ill patients (16), reduce post-trauma capillary leak, and improve gas exchange (17).…”
Section: Introductionmentioning
confidence: 99%
“…However, although some authors suggested that differences in the molecular structure of different starch preparations might be responsible for these inconsistent results [34,35], none of the studies to date was able to determine the mechanistic basics that underlie the possibly antiadherent actions of HES. Regarding the well-preserved expression of adhesion molecules on the endothelium [31,32] as well as on the leukocyte [38], effects on protein synthesis or expression do not seem to play a role. Because HES had an immediate effect on PMN adhesion in our experiment only when it was present during perfusion, we suggest that HES affects leukocyte-endothelial interactions by a direct inhibition of ligand-receptor binding.…”
Section: Discussionmentioning
confidence: 99%
“…According to the manufacturer´s instructions, gelatine is hydrolyzed after implantation of the gelatine-coated prosthesis (18). Investigations in plasma-expanding fluid revealed only a marginal PMN receptor upregulation (CD 11b) under the effect provided by gelatine (19). Wilhelm et al (20) verified the strongest antigen-restricted immune response induced by gelatine-coated.…”
Section: Discussionmentioning
confidence: 93%